A Review on Clinical Data Mining (International Journal of Engineering and Computer Science, 2016)
vClinical data mining is a practice based research strategy by which practitioners and researchers retrieve, analyze and interpret available qualitative and quantitative information from available medical records. It is an active interdisciplinary area of research that is considered the consequent of applying artificial intelligence and data mining concepts to the field of medicine and health care. The aim of this work is to provide a review on the foundation principles of mining clinical dataset, and present the findings and results of past researches on utilizing data mining techniques to mine health care data and patient records. The scope of this article is to present a brief report on preceding investigations made in the sphere of mining clinical data, the techniques applied and the conclusions recounted. The most recent research findings that can further unveil the potential of data mining in the realm of health care and medicine are clearly presented in this review.